Virtuous accomplices in international criminal law - Jackson, M (Cambridge University Press, 2019)
Humanitarian actors sometimes have to decide whether to render assistance in situations that put them at risk of liability for aiding and abetting under international criminal law. This is the problem of the virtuous accomplice—the idea that knowingly contributing to the wrongdoing of others might, exceptionally, be the right thing to do. This article explains why the problem arises and clarifies its scope, before turning to criminal law in England and Wales and Germany to assess potential solutions. It argues that the best approach is to accept a defence of necessity—of justified complicity—and shows that such an argument works in international criminal law.